Isolated fetal echogenic bowel in a retrospective cohort: The role of infection screening. (December 2018) - Masini, Giulia; Maggio, Luana; Marchi, Laura; Cavalli, Iolanda; Ledda, Cristina; Trotta, Michele; Pasquini, Lucia
Abstract: Objective: Fetal echogenic bowel (FEB) is an ultrasonographic marker of fetal infection. We aimed to determine the utility of infection screening when FEB is isolated. Study design: Retrospective observational study of isolated FEB cases between 2006–2014. Infection screening included toxoplasmosis, rubella, syphilis, cytomegalovirus (CMV), herpes simplex virus and parvovirus B19. Fetal karyotyping, screening for cystic fibrosis (CF) and follow-up scans were also offered, according to international standards. Incidence of infection and 95% confidence interval (CI) were calculated. Results: 148 patients with 154 fetuses were included. 4.7% of mothers developed acute infection: four patients developed CMV infection (2.7%, 95% CI 1.1–6.9%), in two fetuses infection was confirmed with amniocentesis and pregnancies were terminated; Parvovirus B19 infection was detected in 2 patients (1.4%, 95% CI 0.4–5.0) and confirmed in one fetus, which developed anemia; there was one toxoplasmosis maternal infection (0.7%, 95% CI 0.1–3.8%) treated with spyramicin, whose fetus was not infected. Percentage of chromosomal/genetic abnormalities was 3.2%, CF 1.3%, intra-amniotic bleeding 1.3%, FGR 34% and other ultrasonographic abnormalities at follow-up scans 18%. Conclusions: The association between isolated FEB and fetal infection is uncommon (1.9% in our population). CMV maternal infection screening is supported by our findings, whereas screening for other infections needs to be further investigated.